Investment by two Nepalese states in the 'Chief Minister's Climate Smart Agriculture Village Model Program' - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Two States of Nepal implement Climate Smart Village Approach allocating Rs. 368 million per year and target to cover 697,207 hectares of agricultural land and 6 million farming population in five years.